2021
DOI: 10.1039/d1ra03750a
|View full text |Cite
|
Sign up to set email alerts
|

Substitution reactivity and structural variability induced by tryptamine on the biomimetic rhenium tricarbonyl complex

Abstract: The biomimetic tryptamine rhenium tricarbonyl complex shows rapid substitution reactivity on the 6th position as well as cytotoxicity and photoluminescence capability induced by the salicylidene bidentate ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
1
1
Order By: Relevance
“…In a previous study, the photoluminescence of seven fac -Re( i ) tricarbonyl complexes showed similar maximum emission wavelengths, regardless of the ancillary ligand tested (including pyridine, imidazole, or triphenylphosphine). 17 By contrast, we found differences in the emission of R1, R2, R4, R5, R6, R8, and R10 with R3, R7, and R9, showing that, in our case, the ancillary ligand does exert an impact on the photoluminescent properties. This result can be mainly attributed to the presence of IHB in the corresponding ancillary ligand, as described above, remarking the importance of this intramolecular interaction regarding the emission behavior.…”
Section: Resultscontrasting
confidence: 67%
“…In a previous study, the photoluminescence of seven fac -Re( i ) tricarbonyl complexes showed similar maximum emission wavelengths, regardless of the ancillary ligand tested (including pyridine, imidazole, or triphenylphosphine). 17 By contrast, we found differences in the emission of R1, R2, R4, R5, R6, R8, and R10 with R3, R7, and R9, showing that, in our case, the ancillary ligand does exert an impact on the photoluminescent properties. This result can be mainly attributed to the presence of IHB in the corresponding ancillary ligand, as described above, remarking the importance of this intramolecular interaction regarding the emission behavior.…”
Section: Resultscontrasting
confidence: 67%
“…Literature for speciation studies is aligned with the experimental trends of 1 and 2 highlighting the substitution of the chloro co-ligands occurs more readily in predominately aqueous media as opposed to organic media. [32] Structural elucidations of the novel free-ligand, Hguabs • Cl, metal complexes 1 and 2 were confirmed by mass spectrometry and elemental analysis, see Figures S12-S14. More specifically, the experimental EA data of the respective metal show the presence of solvent molecules of recrystallization.…”
Section: Synthesis and Spectral Characterizationmentioning
confidence: 85%
“…Indicatively, relatively clear isosbestic points at 379 nm for 1 and 367 nm for 2 show the corresponding Re‐DMSO species in the solution. Literature for speciation studies is aligned with the experimental trends of 1 and 2 highlighting the substitution of the chloro co‐ligands occurs more readily in predominately aqueous media as opposed to organic media [32] …”
Section: Introductionmentioning
confidence: 85%
“…Here we show that from a more chemical perspective the metal complexes at the three main sites (His15, Asp101 and Asp119) have demonstrated their stability as the final products of formation within a biological system over a 38-week period. Additionally, past kinetic evaluations of fac-[Re(CO) 3 ] + complexes bound to nitrogen-and oxygen-based ligand systems have a high rate of formation kinetic constants indicating their kinetic stability (Jacobs et al, 2021).…”
Section: Additional Rhenium Atom Positionsmentioning
confidence: 99%